Analysis Of Comparison The Composite Stock Price Index Before And After Increasing The Investment Grade At Indonesia Stock Exchange - M. Resyah Damaisar S. Salengke Damaisar Salengke (IAIN Manado, 2018)
AbstractCapital markets are economic entities that have a large influence on economic growth. The capital market is one of the containers of transactions in carrying out economic functions for a country. The growing capital market has caused investors to focus on investing in the Indonesian capital market, especially in the business community. The term investment grade refers to a rating that refers to government or corporate debt, has a low ralative ratio of default or default so that it has a sustainable level of trust in the long term he increase in Indonesia's Investment Grade rating is expected to have a positive impact on the Composite Stock Price Index on the Indonesia Stock Exchange which will attract investors to transact in the Indonesian capital market. Based on the results of the research and discussion that has been carried out in the previous chapter, it can be concluded that there are significant differences in the Composite Stock Price Index 30 days before and 30 days after the Investment Grade rating rises on the Indonesia Stock Exchange. Keywords: Composite Stock Price Index, Investment Grade